Estudo das condições reacionais na produção de D-Tagatose catalisada por L-Arabinose isomerase - Oliveira, Ravena Casemiro (2019)
D-Tagatose is a rare sugar with a low caloric value, similar to sucrose, which has 92% of sweetness, but only 38% of the caloric value, approximately 1.5 kg.cal-1. It is considered an antihyperglycaemic agent, due to its low absorption and metabolism by the human organism. In addition, it has several benefits, such as its high antidiabetic potential for the treatment of type II diabetes and prebiotic effect. D-Tagatose can be produced by the enzymatic method from D-Galactose using as the biocatalyst the enzyme L-arabione isomerase. The L-AI enzyme used in this work was obtained from Enterococcus faecium expressed in Escherichia coli. In order to optimize the production of D-Tagatose by biological processes the isomerization reaction was studied. An experimental design of type 2³ with 3 replicates at the central point was carried out to analyze and find the best conditions of pH, temperature and initial concentration of substrate that achieve the highest conversion of D-Galactose in D-Tagatose. In addition, alternative techniques, such as the use of ultrasound and borate buffer were also analyzed. The concentration of D-Tagatose produced was determined by the colorimetric method using spectrophotometer. The results showed that there is a high influence of temperature and pH on the enzymatic reaction. The experimental design resulted in optimum D-Tagatose production at 55 ° C, pH 5.6 and substrate concentration of 164 mM reaching a yield of 29,77 %. It can also be seen that ultrasound increased the effect of temperature on the reaction. In addition, the work indicates that the enzymatic reaction of D-Galactose isomerization in D-tagatose occurs in the temperature range in which the process is non-spontaneous. Thus, it is concluded that the reaction conditions are capable of altering the speed of the enzymatic reaction, but its equilibrium is well defined.